Exercise-induced bronchospasm in soccer athletes living in a tropical humid region - Mousinho Gomes, R. L.; de Albuquerque Rodrigues Filho, E.; de Valois Correia Júnior, M. A.; Batista, G. R.; Souza de Almeida, A. H.; Rizzo, J. A. (Journal of Sports Medicine & Doping Studies, 2018)
Background: Exercise-induced bronchospasm (EIB) is frequent in asthmatic athletes and, although less prevalent, also occurs in non-asthmatic ones. Breathing warm-humid air reduces this phenomenon. Objective: To evaluate EIB prevalence in semi-professional soccer athletes from a tropical humid region. Methods: We included athletes from a soccer team from the city of Recife-Brazil. A history of asthma or respiratory symptoms after exercise, demographic data and baseline FEV1 measurements were obtained. Thereafter, each athlete performed a standardized free field running to achieve 85% to 95% of the maximum calculated heart rate for the last 6 minutes of a total running time of 8 to 10 minutes. FEV1 was measured again at 5, 10, 15 and 30 minutes after exercise and EIB was defined as a reduction = 10% from basal values in two consecutive time points. Results: Fifty-four male athletes aged between 13 and 21 years were evaluated. All denied exercise associated respiratory symptoms. Mean temperature and air humidity were 30.2°C ± 2.7°C and 82.1% ± 2.9%, respectively. EIB was found in two (7%) athletes (with a fall in FEV1 from baseline of 23.3% and 22.6%), none with history of asthma symptoms. Two other athletes had a history of asthma symptoms in childhood but no decrease in FEV1. Conclusion: The studied population of semi-professional soccer athletes with no exercise associated respiratory complaints showed a low BIE prevalence (7%). It may be necessary to perform the challenge with the athlete breathing dry air in those that also play in more dry and cold climates.